Embracing Minimalism: A Guide to Modern Graphic Design Practices - Osaigbovo, Felix Onaiwu (VCD, 2024)
Over time, the practice of graphic design has been undergoing progressive changes so much so that various authorities have come up with various specifications. There are various types of graphic designs amongst which are web design, user interface and user experience design, advertising and marketing design, game design, motion graphics, cartoons and animations, illustrations and typography, and publication design to mention but a few. This topic extrapolates the nuances of a minimalist approach to modern graphic design and in this essay; the word “graphics” has been used as a generic term that encapsulates corporate designs of items such as news magazines, journals, annual reports, calendars, book cover designs and such like. The objective of this research is to bring to the fore and compartmentalize the various stages of the minimalist approach to creating a cutting-edge modest design. The research methodology employed for this study is studio-based and practice-led, the survey and quasi-ethnographic study with some touch of literature review. Discussion exclusively centered on the antecedents of minimalism and steps to be taken in achieving a catchy design using the simplest techniques possible while it was concluded that it is more advantageous to adopt the minimalist approach to graphic designs with reasons rightly highlighted and expatiated on.